Antioxidant properties of guava fruit : comparison with some local fruits - Lim, Yau Yan; Lim, Theng Teng; Tee, Jing Jhi (Sunway University College, 2006)
Two varieties of guava fruit were analyzed for total phenol contents, ascorbic acid contents and antioxidant activities. The antioxidant activities were assessed based on the ability of the fruit extracts in 50% ethanol to scavenge DPPH, reduce Fe(III) to Fe(II) and to bind to Fe(II) ion. The results were compared to several other local fruits as well as orange. It was found that the guava fruit contains relatively high amounts of antioxidant. It also has high primary, but low secondary antioxidant potential. Storage at 4oC has the effect of increasing ascorbic acid content, and the non-peeled fruit has higher total phenol and ascorbic acid contents compared to the peeled fruit. The length and width of the seedy guava were also monitored over a period of 17 weeks to define specific stages of fruit ripening.